Utility and limitations of exome sequencing as a genetic diagnostic tool for children with hearing loss. (December 2018) - Sheppard, Sarah; Biswas, Sawona; Li, Mindy; Jayaraman, Vijayakumar; Slack, Ian; Romasko, Edward; Sasson, Ariella; Brunton, Joshua; Rajagopalan, Ramakrishnan; Sarmady, Mahdi; Abrudan, Jenica; Jairam, Sowmya; et al.
Abstract Purpose Hearing loss (HL) is the most common sensory disorder in children. Prompt molecular diagnosis may guide screening and management, especially in syndromic cases when HL is the single presenting feature. Exome sequencing (ES) is an appealing diagnostic tool for HL as the genetic causes are highly heterogeneous. Methods ES was performed on a prospective cohort of 43 probands with HL. Sequence data were analyzed for primary and secondary findings. Capture and coverage analysis was performed for genes and variants associated with HL. Results The diagnostic rate using ES was 37.2%, compared with 15.8% for the clinical HL panel. Secondary findings were discovered in three patients. For 247 genes associated with HL, 94.7% of the exons were targeted for capture and 81.7% of these exons were covered at 20× or greater. Further analysis of 454 randomly selected HL-associated variants showed that 89% were targeted for capture and 75% were covered at a read depth of at least 20×. Conclusion ES has an improved yield compared with clinical testing and may capture diagnoses not initially considered due to subtle clinical phenotypes. Technical challenges were identified, including inadequate capture and coverage of HL genes. Additional considerations of ES include secondary findings, cost, and turnaround time.